A long time gone - White, Karen (Karen S.) (New American Library, 2014)
"When Vivien Walker left her home in the Mississippi Delta, she swore never to go back, as generations of the women in her family had. But in the spring, nine years to the day since she'd left, that's exactly what happens--Vivien returns, fleeing from a broken marriage and her lost dreams for children. What she hopes to find is solace with "Bootsie," her dear grandmother who raised her, a Walker woman with a knack for making everything all right. But instead she finds that her grandmother has died and that her estranged mother is drifting further away from her memories. Now Vivien is forced into the unexpected role of caretaker, challenging her personal quest to find the girl she herself once was. But for Vivien things change in ways she cannot imagine when a violent storm reveals the remains of a long-dead woman buried near the Walker home, not far from the cypress swamp that is soon to give up its ghosts. Vivien knows there is now only one way to rediscover herself--by uncovering the secrets of her family and breaking the cycle of loss that has haunted her them for generations"--